Respuesta :

EQUATION

=============================

[tex]\large\bold{Equation:}[/tex]

  • [tex]\large\sf{F(4p + 3) = 8 - 5(4p + 3)}[/tex]

[tex]\large\bold{Solution:}[/tex]

Let's solve for f

[tex]\large\sf{F(4p + 3) = 8 - 5(4p + 3)}[/tex]

1st step: Factor out variable f

  • [tex]\large\sf{F(4p+3)=āˆ’20pāˆ’7}[/tex]

2nd step: Divide both sides by 4p+3

  • [tex]\large\sf{ \frac{F(4p + 3)}{4p + 3} = \frac{ - 20p - 7}{4p + 3} }[/tex]

  • [tex]\large\sf{F = \frac{ - 20p - 7}{4p + 3} }[/tex]

[tex]\large\bold{Answer:}[/tex]

  • [tex]\large\tt{F = \frac{ - 20p - 7}{4p + 3} }[/tex]

===================================

How is it? Hope you appreciate and understand my answer. Have a great and nice day ahead!!

^^